Stigma and Family Knowledge of Tuberculosis Patients at Naibonat and Oesao Health Center - Lay, Kenangan Y. Y.; Manurung, Imelda F. E; Landi, Soleman (Timorese Journal of Public Health, 2020)
Stigma in tuberculosis can cause delays in treatment and hurt the continuity of treatment so that treatment is not completed. Knowledge about tuberculosis that is known by the family will increase efforts to prevent or spread tuberculosis to other families in the house and the environment around the house. The purpose of this study was to determine the stigma and knowledge of the family of tuberculosis patients. This study is a descriptive study with an approach cross-sectional. The sample in this study amounted to 61 people representing patients who were being treated at the Oesao Health Center and the Naibonat Health Center. The results of the study show that the stigma that occurs in the families of tuberculosis patients is a lack of knowledge about tuberculosis, the causes of tuberculosis, how it can be infected, and how to treat it, where people still think that tuberculosis is a man-made disease so that if there is one family who is sick they will be sick first. In the past, they looked for people to pray instead of checking themselves into health facilities such as health centers. Family knowledge about tuberculosis is good, where family knowledge is obtained from counseling health workers at the health center and at the Integrated Health Center so that families can prevent the transmission of tuberculosis in the family and the environment around the tuberculosis patient's home. It is recommended to improve counseling, personal hygiene, and Clean and Healthy Life Behavior to prevent the spread of tuberculosis to families and other people around the home environment.